(3GdQSGdJGf GdSjfjI hGdTjfjIs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s ((3YHO GdZfi Hf Ydi Hf EHQGgje GdebQF s)
(3ChdgG (B:s
(3JHOC GdQSGdI GdChdi (B( (3HGSe GdbOhS CSJaJM (B) (3, hChd GdQSGdI GdKGfjI (B( (3HETGO GdefTF CfTF (B) s
(3BNQgG (B:s
(3hJfJgi GdQSGdI GdChdi H` (B( (3hMSHfG GdSdGe hSdGeg dQShd GdESdGe (B) (3, hJfJgi H` (B( (3hJTQjag dHTjQ GdHTQ hTajY GdeMTQ (B) (3fLRJ GdQSGdJGf s
(3GdfSNI HgG MhGTs
(3YdjgG ELGRI GHf HQi ddfGSNs
(3cJHgG GdfGSN ef CUd Hf HQis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs